PENGATURAN PERATURAN PRESIDEN NOMOR 72 TAHUN 2021 TENTANG PERCEPATAN PENURUNAN STUNTING DAN IMPLEMENTASINYA DI KECAMATAN MAULAFA KOTA KUPANG - Mbengu, Yosep F; Meyners, David Y; Ermalinda, Jenny (Petitum Law Journal, 2024)
This research was carried out in Maulafa District, Kupang City in November 2023 until completion. The formulation of the problem in this research is: How are Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction and its Implementation in Maulafa District, Kupang City, and What are the efforts of the Maulafa District Government in handling Stunting.This research uses normative juridical and empirical juridical research methods. The data collection techniques used are: Interviews, Study of documents/literature in the form of books, legislation, journals and other written materials related to the research topic. The data analysis technique is, all information that has been processed is analyzed using normative juridical and empirical juridical methods in accordance with the data obtained while still paying attention to theories, principles and legal rules relating to Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction and its Implementation in Maulafa District, Kupang City. Suggestions in this writing: The government needs to make additional regulations or efforts in handling cases of stunting. Based on the data obtained, it is stated that the low level of community participation in preventing stunting is one of the causes of the high stunting rate in Maulafa sub-district.